Age of air from in situ trace gas measurements: insights from a new technique - E. A. Ray; E. A. Ray; F. L. Moore; F. L. Moore; H. Garny; H. Garny; E. J. Hintsa; E. J. Hintsa; B. D. Hall; G. S. Dutton; G. S. Dutton; D. Nance; et al. (Atmospheric Chemistry and Physics)
The age of air is an important transport diagnostic that can be derived from trace gas measurements and compared to global chemistry climate model output. We describe a new technique to calculate the age of air, measuring transport times from the Earth's surface to any location in the atmosphere based on simultaneous in situ measurements of multiple key long-lived trace gases. The primary benefits of this new technique include (1) optimized ages of air consistent with simultaneously measured SF6 and CO2; (2) age of air from the upper troposphere through the stratosphere; (3) estimates of the second moment of age spectra that have not been well constrained from measurements; and (4) flexibility to be used with measurements across multiple instruments, platforms, and decades. We demonstrate the technique on aircraft and balloon measurements from the 1990s, the last period of extensive stratospheric in situ sampling, and several recent missions from the 2020s, and compare the results with previously published and modeled values.